If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (10a + 3) + (9a + 2) = 0 Reorder the terms: (3 + 10a) + (9a + 2) = 0 Remove parenthesis around (3 + 10a) 3 + 10a + (9a + 2) = 0 Reorder the terms: 3 + 10a + (2 + 9a) = 0 Remove parenthesis around (2 + 9a) 3 + 10a + 2 + 9a = 0 Reorder the terms: 3 + 2 + 10a + 9a = 0 Combine like terms: 3 + 2 = 5 5 + 10a + 9a = 0 Combine like terms: 10a + 9a = 19a 5 + 19a = 0 Solving 5 + 19a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 19a = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 19a = 0 + -5 19a = 0 + -5 Combine like terms: 0 + -5 = -5 19a = -5 Divide each side by '19'. a = -0.2631578947 Simplifying a = -0.2631578947
| 36x^2+12x=-1 | | 49-14n+n^2=0 | | 64-3g^2-2= | | 9n+n-3n=14 | | -8=w+-10 | | 135=6(4x-2)-3x | | 3+4x=-41 | | 10x+1.25=100 | | b-7(4b-1)+b= | | -15+r=-8 | | -2m+4m-7=9 | | 3j+5k+3j+8k= | | 2x^3-8x^2+8x-6=0 | | -2x+25=3x-6 | | 4x+5968*3=0 | | C+4c=-90 | | mx^2-2x-m-1=0 | | 6x-10=-34 | | 7ab+ab-9ab= | | 0.66a=6 | | 3x+0+8=0 | | 3x^3-13x^2+12x-6=0 | | 9x-7y=y | | 10x-y=12 | | X+.75y=15 | | -(8-b)+12b-9=-6b+2b | | 1=x-6 | | 3(2x-1)+2=5x-1 | | x+4y+2z=0 | | 2x-3y+2=2 | | 6+4a=-8 | | 0.66r=8 |